Carbon Nanotube Mat Reinforced Thermoplastic Composites with a Polymerizable, Low-Viscosity Cyclic Butylene Terephthalate Matrix - Noh, Ye Ji; Kim, Han Sang; Kim, Seong Yun (SPRINGER, 2014)
A fabrication method was developed to enhance the processability of a thermoplastic composite reinforced with a carbon nanotube (CNT) mat using an in situ polymerizable low-viscosity cyclic butylene terephthalate (CBT) oligomer. We obtained excellent electrical, thermal, and mechanical properties in the in-plane direction of the prepared CNT mat composites. For the CNT mat composites, the highest thermal diffusivity of 1.53x10(-5) m(2)/s was obtained in the in-plane direction due to the continuously and fully connected CNTs within the CNT mat filler and the value was higher than that of alumina. The properties depended on the internal structure of the composites, such as the development of the morphology, waviness, and weight fraction of the CNT mat within the composites. These excellent properties were revealed under optimum processing conditions with combined high compression pressure, short processing time, and quenching to induce an ideal structure in the CNT mat within the composites.
Keywords: MECHANICAL-PROPERTIES; THERMAL-CONDUCTIVITY; NANOCOMPOSITES; BUCKYPAPER; FILMS; PAPER